Awareness of Rabies Prevention Triad Among Residents of Metropolitan Lima - Dueñas Rodríguez, Falhon (2023)
The objective of this study was to describe the knowledge levels regarding the prevention triad for rabies transmitted by dog bites among residents of Metropolitan Lima. Data were collected from the National Survey of Budget Programs 2020. The classifying variables included district groupings (Lima Norte, Lima Centro, Lima Este, Lima Sur, and Callao) and the socioeconomic stratum of the population (A, B, C, D, and E). The study variables focused on the proportion of residents who were aware of the components of the prevention triad for rabies (washing the wound with soap and water, identifying the biting animal, and seeking medical care). The study found that only 7.2% of respondents were aware of all three components of the prevention triad for rabies. The best-known component was seeking medical care (90.2%), followed by washing the wound with soap and water (49.7%), and identifying the biting animal (26.4%). It was also found that lower socioeconomic strata were associated with lower knowledge of the prevention triad for rabies. The study results emphasize the need to reassess the strategies used to raise awareness among the population of Metropolitan Lima regarding the public health significance of seeking care for dog bites and regarding the prevention triad for rabies.